Mechanism Mekanisme dan Tahapan Penanganan Perkara Perselisihan Hasil Pemilu Presiden dan Wakil Presiden Tahun 2024 - Sony, Edy (Bacarita Law Journal, 2024)
The Presidential and Vice Presidential Elections in Indonesia is a crucial moment in the nation's democratic life. However, in the process, disputes and dissatisfaction with the election results announced by the General Election Commission (KPU) often arise. If not handled properly, this dissatisfaction can threaten political stability and public trust in the democratic system. Therefore, an effective and transparent mechanism for resolving election disputes is crucial to maintain the integrity of the democratic process in Indonesia. The research to conduct an in-depth analysis of the mechanisms and stages of resolving disputes over the results of the Presidential and Vice Presidential elections in Indonesia in 2024, and to assess the impact of the mechanism for resolving election disputes on political electability and public trust. The research method used is normative legal research. Normative legal research studies how legal norms function. The data collection method used is literature review. This study utilizes secondary data obtained from various literature and regulations related to the issues under investigation. The research findings indicate that the mechanisms and stages of resolving election disputes in Indonesia are detailed in the legislation. The level of public trust in the Constitutional Court as the institution for resolving disputes is relatively high, but concerns exist regarding the independence and transparency of the process. There is a need for stricter oversight of the dispute resolution process to ensure that each step is carried out in accordance with applicable regulations. Thus, it is hoped that the mechanism for resolving election disputes in Indonesia can operate more effectively and be trusted by all parties involved.